1990
DOI: 10.1161/01.cir.81.3.790
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-dependent effects of quinidine on the ventricular action potential and QRS duration in humans.

Abstract: We studied the frequency-dependent effects of quinidine on the right ventricular action potential and QRS duration in 10 patients (nine men and one woman; mean age, 57±+14 years) undergoing electrophysiologic studies for clinical indications. The right ventricular monophasic action potential, electrocardiographic, and conventional intracardiac electrical signals from various sites were recorded at different pacing cycle lengths from 30 seconds to 1 minute before and after a 10-mg/kg i.v. quinidine infusion. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…Additionally, dofetilide, Sotalol and quinidine have been found to prolong ventricular repolarization in healthy human hearts (QT duration; Johannsen et al, 2014; Lande et al, 1998; Vicente et al, 2015) and patients (QT duration (Echt et al, 1982; McComb, McGovern, McGowan, Ruskin, & Garan, 1987); monophasic AP recordings (Melicherick et al, 1999; Nademanee et al, 1990; Yuan, Wohlfart, Rasmussen, Olsson, & Blomstrom-Lundqvist, 1994)). Our AP data from healthy donor hearts are in agreement with those reported for dofetilide, Sotalol and quinidine by these groups.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, dofetilide, Sotalol and quinidine have been found to prolong ventricular repolarization in healthy human hearts (QT duration; Johannsen et al, 2014; Lande et al, 1998; Vicente et al, 2015) and patients (QT duration (Echt et al, 1982; McComb, McGovern, McGowan, Ruskin, & Garan, 1987); monophasic AP recordings (Melicherick et al, 1999; Nademanee et al, 1990; Yuan, Wohlfart, Rasmussen, Olsson, & Blomstrom-Lundqvist, 1994)). Our AP data from healthy donor hearts are in agreement with those reported for dofetilide, Sotalol and quinidine by these groups.…”
Section: Discussionmentioning
confidence: 99%
“…Effective refractory period (ERP) represents the maximal interval between the prior stimulation and the following stimulation that cannot develop the next action potential. ERP is usually dependent on action potential duration (APD) (Nademanee et al 1990). In the previous human heart study, repetitive burst stimuli shortened both ERP and APD, and the encroachment of stimuli onto the preceding repolarization phase was associated with induction of tachyarrhythmia (Koller et al 1995).…”
Section: Fig 2 Effects Of Pilsicainide On Action Potential (Bcl 500mentioning
confidence: 99%
“…Although ERP is usually dependent of and shorter than APD (Costard-Jackle and Franz 1989;Nademanee et al 1990), it can be prolonged beyond the repolarization of action potential in some situations. Lazzara et al (1975) reported this phenomenon in the ventricular myocardium and termed it post-repolarization refractoriness (PRR).…”
mentioning
confidence: 99%
“…Additionally, dofetilide, Sotalol and quinidine have been found to prolong ventricular repolarization in healthy human hearts (QT duration;Johannsen et al, 2014;Lande et al, 1998;Vicente et al, 2015) and patients (QT duration (Echt et al, 1982;McComb, McGovern, McGowan, Ruskin, & Garan, 1987); monophasic AP recordings (Melicherick et al, 1999;Nademanee et al, 1990;Yuan, Wohlfart, Rasmussen, Olsson, & Blomstrom-Lundqvist, 1994)). Our AP data from healthy donor hearts are in agreement with those reported for dofetilide, Sotalol and quinidine by these groups.…”
Section: Discussionmentioning
confidence: 99%